DEVELOPMENT OF ACCREDITATION IN RUSSIAN HIGHER EDUCATION: HISTORY AND FUTURE - Vladimir G. Navodnov; Galina N. Motova (Moscow Polytechnic University, 2016)
The article considers the twenty year-old history of accreditation in the system of higher education. The authors argue that socio-economic and demographic conditions determined the specific features of modernization in the structure of higher education and the development of the Russian model of accreditation in the form of institutional evaluation. The reasons for establishing two types of accreditation - state and public-professional - are pointed out. Taking into account the influence of the state educational policy and the expansion of global cooperation, in particular, the Bologna process, three stages of the development of accreditation of higher education institutions and study programmes are identified: innovation stage, European stage and separation stage. Analyzing the experience of the development of the accreditation system as a social phenomenon the authors focus on its specific features, achievements and problems, and also outline the tendencies in its further development.